Demographics, house prices and mortgage design - David Miles (Bank of England, External Monetary Policy Committee Unit, 2012)
This paper develops a model of the housing market that takes account of population density to assess the impact of population changes on the value and size of the housing stock. The model implies that if population density is on an upward trajectory, rises in population and in incomes increasingly generate price response and diminishing rises in the stock of housing. This has implications for the optimal structure of housing finance. It makes equiy financing of home purchase more desirable. The properties of hybrid debt-equity contracts for financing house purchase are explored.
Keywords: J11; R31; R34; 330; demographics; house prices; mortgage design; population density; housing; debt-equity; equity financing